Teacher-Driven Strategies for Enhancing Parental Involvement in Rural Education - Mafu, Lungisani Excellent; Makhonza, Lindokuhle O; Mngomezulu, Thanduxolo Peace (Central European Journal of Educational Research, 2025)
Parental involvement is widely acknowledged as a vital contributor to learners’ academic achievement and overall school success. While much is known about the benefits of parental engagement, particularly in urban and well-resourced settings, the dynamics and challenges in rural schools remain underexplored. This study addresses that gap by investigating how teachers perceive and implement strategies to enhance parental involvement in rural contexts. Specifically, the study aimed to answer the following question: (1) What are teachers’ perceptions and experiences regarding parental involvement in rural schools? and (2) What teacher-driven strategies do they propose to improve collaboration with parents? This qualitative case study draws on Rotter’s Social Learning Theory to explain how behaviour is shaped by observation, reinforcement, and social interaction. The study was conducted at a rural high school in Mandlanzini Agri-village, KwaZulu-Natal, with ten purposively selected teachers as participants. Data were collected through a semi-structured online questionnaire and analysed thematically following Braun and Clarke’s (2006) coding process. The findings reveal a pressing need for structured, teacher-driven strategies that extend beyond standard parent-teacher meetings to include structured and culturally responsive interventions. The study highlights the practical value of teacher agency in facilitating parental involvement and offers context-specific insights that may guide future interventions in similar rural settings.